(untitled) (Research, Society and Development, 2021)
Knowledge of the deleterious effects of passive smoking in dogs is inconclusive and scarce. The present study investigated pulmonary radiographic aspects of dogs exposed to cigarette smoke daily. Thirty dogs were used (15 from households where smoking was reported and 15 dogs from households where there was no smoking), older than two years, regardless of sex, race, skull composition and clinical signs from september 2014 and june 2015. Chest X-rays were taken in all dogs to characterize possible lung lesions with analysis performed in a double-blind study and a questionnaire was applied to the tutors. The analysis of these data provided that 33.33% of passive smoking dogs showed clinical signs like those observed in passive smokers, although there was no significant association between the risk factors. Lung injuries were observed in all passive smoking dogs. The link between dogs, their smoking guardians and respiratory diseases is difficult. This study demonstrates pulmonary radiographic alterations suggestive of bronchial pulmonary disease were observed in 100% of passive smoking dogs. Thus, we can conclude that, regardless of the time of exposure to smoke, living with smokers’ guardians is a risk to the health of animals. Our results suggest the harmful action of exposure to cigarette smoke as a risk factor for lung health in dogs.